2022
DOI: 10.1101/2022.03.16.484578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher visual areas act like domain-general filters with strong selectivity and functional specialization

Abstract: Investigation of the visual system has mainly relied on a-priori hypotheses to restrict experimental stimuli or models used to analyze experimental data. Hypotheses are an essential part of scientific inquiry, but an exclusively hypothesis-driven approach might lead to confirmation bias towards existing theories and away from novel discoveries not predicted by them. This paper uses a hypothesis-neutral computational approach to study four high-level visual regions of interest (ROIs) selective to faces, places,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 89 publications
(160 reference statements)
2
16
0
Order By: Relevance
“…Some theoretical accounts of these regions consider these as independent and unrelated functional modules, implicitly assuming no direct relationship between them ( Kanwisher, 2010; Zeki, 1978 ) . However, the integrated feature space of the deep neural network allows us to consider an alternate hypothesis that face- and scene-selectivity might naturally emerge as different parts of a common encoding space—one whose features are designed to discriminate among all kinds of objects more generally (Konkle & Caramazza, 2013; Bao et al, 2020; Vinken et al, 2022; Prince & Konkle, 2020; Khosla & Wehbe, 2022). If this is the case, these categories would drive responses in a localized part of the feature space, which would emerge as a localized cluster of selective responses in the SOM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some theoretical accounts of these regions consider these as independent and unrelated functional modules, implicitly assuming no direct relationship between them ( Kanwisher, 2010; Zeki, 1978 ) . However, the integrated feature space of the deep neural network allows us to consider an alternate hypothesis that face- and scene-selectivity might naturally emerge as different parts of a common encoding space—one whose features are designed to discriminate among all kinds of objects more generally (Konkle & Caramazza, 2013; Bao et al, 2020; Vinken et al, 2022; Prince & Konkle, 2020; Khosla & Wehbe, 2022). If this is the case, these categories would drive responses in a localized part of the feature space, which would emerge as a localized cluster of selective responses in the SOM.…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, Huang et al, (2022) have found that information about the real-world size of objects is encoded along the second principal component of the late stages of deep neural networks ( 44 ). Further, Vinken et al, 2022 recently demonstrated that face-selective neurons in IT could be accounted for by the feature tuning learned in these same object-trained deep neural networks (( 45 ), also see ( 42 , 46 , 43 )). Thus, deep neural networks clearly operationalize a multi-dimensional representational encoding space that has information about these well-studied object distinctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, some researchers are trying to build accurate encoding models that, in essence, enable simulations of neuroscience experiments [44,45]. This type of modeling is especially important in cases when experimental data are expensive or hard to obtain: with a high-accuracy model of brain responses, a researcher can run thousands of experiments in silico, refine their hypothesis, and then test the critical predictions in vivo.…”
Section: Build Maximally Accurate Models Of Brain Datamentioning
confidence: 99%
“…Finally, some researchers are trying to build accurate encoding models that, in essence, enable simulations of neuroscience experiments [44, 45]. This type of modeling is especially important in cases when experimental data are expensive or hard to obtain: with a high-accuracy model of brain responses, a researcher can run thousands of experiments in silico , refine their hypothesis, and then test the critical predictions in vivo .…”
Section: How Do Neuroscientists Use Mapping Models?mentioning
confidence: 99%